Integrated Management of Tikka Disease in Groundnut Using Chemical, Botanical, and Biocontrol Approaches - Nawaz, Muhammad; Haq, M. Inam ul; Ali, Syed Zulfiqar; Irshad, Gulshan; Rehman, Atta ul; Zahra, Mehak; Aslam, Hurmain; Noor, Laiba Zarar; Tahir, Muhammad Naveed (Journal of Agriculture and Veterinary Science, 2025)
Groundnut (Arachis hypogaea) in Pakistan faces a major challenge from tikka disease, caused by Cercospora arachidicola and Cercosporidium personatum. The present study was undertaken to isolate the causal agents and evaluate the efficacy of fungicides and Bio-botanical protectants. Infected leaf samples were collected from the University Research Farm, Koont (Chakwal), and pathogens were isolated based upon cultural and morphological characteristics (e.g., colony color, texture, spore size and shape). Pathogenicity was confirmed by fulfilling Koch’s postulates proving Cercospora arachidicola and Cercosporidium personatum to be the actual cause for tikka disease of ground nut. Following isolation, pot experiment was conducted under Completely Randomized Design (CRD) comprising nine treatments and three replications. Means were analysed statistically by applying ANOVA using Statstix 8.1 software. Varying concentrations of Mancozeb (0.1% and 0.2%), neem extract (5% and 10%), garlic extract (5% and 10%), and Trichoderma spp. (5 mL and 10 mL), with combined treatments of Mancozeb 0.2%, neem 10%, garlic 10%, and Trichoderma 10 mL. Key parameters viz., disease incidence, severity, plant height, number of leaves, fresh and dry biomass were recorded. The results revealed combined treatments effectively reducing disease incidence by 48.66% and severity by 50.59% and enhancing plant height (30.32 cm), leaf number (15), and biomass. The disease was supressed highly using 0.2% Mancozeb, followed by moderate Trichoderma treatments while neem and garlic extracts showed minimum potential. The study highlighted combined biogenic inputs to manage tikka disease and improve plant growth with effectivity, sustainability, and eco-friendly strategies.Keywords: Groundnut, Cercospora arachidicola, Cercosporidium personatum, Mancozeb, Trichoderma, Botanicals, Biocontrol.
Keywords: Groundnut; Cercospora arachidicola; Cercosporidium personatum; Mancozeb; Trichoderma; Botanicals; Biocontrol